Peak systolic velocity thresholds of cavernosal penile arteries in patients with and without risk factors for arterial erectile deficiency. (1st July 2016) - Cavallini, G.; Scroppo, F. I.; Zucchi, A.
Summary: To simultaneously assess the peak systolic velocity (PSV) and the end‐diastolic velocity (EDV) at dynamic duplex examination of the cavernosal penile arteries, and penile rigidity in subjects with satisfactory erectile function with and without risk factors for arterial erectile deficiency (ED). This multicenter prospective study examined two populations having satisfactory sexual function with dynamic duplex examination of the cavernosal arteries; one population had risk factors for arterial ED (65 patients, Group 1) and the other (60 patients, Group 2) had no risk factors. Penile rigidity was assessed using the Schramek grading system score (SGSS). The PSV, the EDV, and the SGSS values of Group 1 and of Group 2 were measured and compared using analysis of variance. The EDV and PSV data presented in this abstract are the arithmetical means of the data of the left and right cavernosal arteries. The Group 1 patients showed a mean ± standard deviation PSV of 26.4 ± 13.2 cm/sec and the Group 2 patients showed a PSV of 44.7 ± 9.6 cm/sec ( p  = 0.002). The EDV of Group 1 was −15.6 ± 16.1 cm/sec and the EDV of Group 2 was −14.9 ± 13.7 cm/sec ( p  = 0.329). The SGSS in Group 1 was 3.2 ± 0.3 and the SGSS in Group 2 was 4.8 ± 0.2 ( p  = 0.008). Intra‐ and inter‐operator variability were not statistically significant. The PSVs and the SGSSs of patients with risk factors for ED and satisfactory erectile function were subnormal and significantly lower than the PSVs and the SGSSs of patients without risk factors. It has been hypothesized that compensatory mechanisms, probably of psychological origin, might allow satisfactory erectile response, even in the presence of a subnormal PSV.